Challenges and Developments of High Energy Density Anode Materials in Sulfide‐Based Solid‐State Batteries. Issue 24 (15th December 2022) - Li, Dabing; Liu, Hong; Liang, Yuhao; Wang, Chao; Fan, Li‐Zhen
Abstract: All‐solid‐state batteries (ASSBs) are considered the most promising next‐generation energy storage device owing to their high safety. The sulfide solid electrolytes (SEs) possess high ionic conductivity (10 −4 –10 −2  S cm −1 ) at room temperature, non‐flammable properties, and moderate modulus, all of which are crucial requirements for the scalable application of high‐performance ASSBs. However, achieving a high energy density of >300 Wh kg −1 appears to be a significant hurdle in current ASSBs. Research on high‐energy‐density anode materials is of great importance for enhancing the overall energy density in ASSBs. However, relatively few review articles have focused on the overall development profile of representative anode materials in sulfide SEs. Here, we start by underlining the importance of the multi‐physical properties of sulfide SEs, including ionic conductivity, chemical properties, and mechanical properties. Furthermore, the potential failure mechanisms of sulfide SEs with Li anodes and corresponding improvement strategies are systematically discussed. Finally, we summarize recent notable works of anode materials in sulfide‐based ASSBs, aiming to provide important guidance for fulfilling a real leap of high energy density anode materials in sulfide ASSBs. Abstract : Sulfide‐Based Solid‐State Batteries : To realize the extensive commercialization of high energy density anode materials in all‐solid‐state batteries, the review begins with a discussion of the various physical properties of sulfide solid electrolytes and future research directions. The failure mechanism and corresponding improvement strategies of lithium metal anodes are summarized and recent notable works of high‐energy anode materials are also introduced. The review provides important guidance for high‐performance anode materials in sulfide‐based all‐solid‐state batteries.